The Horoscopic Place: The Encounter between Astrologer and Client. (15th February 2019) - Gunzburg, Darrelyn
Abstract : This article investigates whether astrology is an alternative spiritual practice associated with divination, an occurrence beyond normal human experience. Between July 2015 and July 2016 I conducted semi-structured interviews with seven astrologers who had each been practicing, writing, and teaching astrology for twenty-ﬁve years or more. The interviews concentrated on understanding the space set aside by the astrologers to focus on the horoscope. The results revealed that the astrologers considered the repetitive behaviour of preparation for the consultation a ritual, reﬂecting Emile Durkheim's views that a special place set aside and reinforced by ritual became sacralised. As the astrologers discussed the storied landscape of the horoscope, a moment of recognition by the client allowed the astrologer to see more deeply into what Henri Lefebvre called the lived space of the imagination. The ensuing conversation opened the way to a much greater depth of understanding between both astrologer and client and generated insights that did not require a connection with the supernatural.